The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s12070-008-0105-y
|View full text |Cite
|
Sign up to set email alerts
|

Histological study of routine tonsillectomy specimen

Abstract: Introduction Palatine and nasopharyngeal tonsils are lymphatic fl esh clusters of tissue of the respiratory and digestive tract's epithelium.There is not much literature pertaining to the histological assessment of resected tonsils though anecdotal case reports of choristoma, squamous cell cysts of the tonsil have been reported which mimicked chronic tonsillitis. Tonsils also are an important site for head and neck cancer in adults.Aim & objective To study the histological features of routine tonsillectomy spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Tonsil develops from the second pharyngeal pouch, epithelium develops from the ectoderm, and lymphoid tissue from the mesoderm. 1 In our study, histological examination of 154 pediatric tonsils showed no evidence of malignancy or tuberculosis. In a study done by Brien 2 in 2010, malignancy was diagnosed in 0.026% of pediatric patients.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Tonsil develops from the second pharyngeal pouch, epithelium develops from the ectoderm, and lymphoid tissue from the mesoderm. 1 In our study, histological examination of 154 pediatric tonsils showed no evidence of malignancy or tuberculosis. In a study done by Brien 2 in 2010, malignancy was diagnosed in 0.026% of pediatric patients.…”
Section: Discussionsupporting
confidence: 45%
“…Cartilaginous choristoma in tonsil has been recorded. 1 Osteo-cartilaginous choristoma is very rare in tonsil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the knowledge of the histological aspects of tonsils and adenoids and the distribution of immune elements involved in chronic inflammation may lead to the identification of pathogenic pathways of initiation, persistence or remission of lesions. Microscopic evaluation can also improve imaging techniques and treatment criteria, as well as the associated morbidity rate [ 20 ], especially in the conditions in which the impact of the deprivation of the child’s organism of numerous immunocompetent cells by radical surgical technique is not yet known [ 5 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…The usual indication for surgical resection of tonsils is chronic recurrent tonsillitis. Literature also does not indicate the reason behind the fact that only part of the population suffers from recurrent chronic tonsillitis in spite being exposed to similar conditions [1].…”
Section: Introductionmentioning
confidence: 99%